Kolaborasi Aktor dalam Pemberdayaan Masyarakat Selama Pandemi Covid-19 Desa Jelgung Kabupaten Sampang - Endik Hidayat; Aufa Izzudin Baihaqi; Rustono Farady Marta (Warta LPM, 2022)
Changes in social life due to the Covid-19 pandemic also have an impact on the village level. The research carried out aims to review the model of community empowerment in the Covid-19 pandemic in Jelgung Village. As for the two questions that arise, what is the model of community empowerment of the Jelgung village government? Who are the actors involved in community empowerment in Jelgung village during the Covid-19 pandemic? This study will use qualitative methods, more specifically descriptive analysis at the village level. Qualitative data was obtained through in-depth interviews with informants consisting of actors involved in empowering village residents, namely village heads, village officials and community leaders. The results showed that empowerment in Jelgung village was driven by two main actors, namely individuals from community leaders and local and village governments. Meanwhile, empowerment activities are divided into two forms, namely labor intensive including training and capital intensive including small and medium business capital assistance.